1996
DOI: 10.1210/jcem.81.6.8964857
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and adrenocorticotropin response to desmopressin in women with Cushing's disease compared with depressive illness.

Abstract: The pituitary-adrenal responsiveness to desmopressin of women with depressive illness was compared with that of patients with Cushing's disease, who are known to be highly responsive, and to that of normal controls, who are known to be poorly responsive to the peptide. Although 100% of the patients in the group with Cushing's disease met the response criterion with cortisol increases of 632 +/- 80 nmol/L above baseline (mean +/- SE), the prevalence of responders was 36% in the depressive group and 10% in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…It has been reported that desmopressin test is able to differentiate patients with Cushing's disease from the majority of normal subjects and patients with obesity, depression or pseudo-Cushing states [14,16,17,[22][23][24]. It has been reported that desmopressin test is able to differentiate patients with Cushing's disease from the majority of normal subjects and patients with obesity, depression or pseudo-Cushing states [14,16,17,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that desmopressin test is able to differentiate patients with Cushing's disease from the majority of normal subjects and patients with obesity, depression or pseudo-Cushing states [14,16,17,[22][23][24]. It has been reported that desmopressin test is able to differentiate patients with Cushing's disease from the majority of normal subjects and patients with obesity, depression or pseudo-Cushing states [14,16,17,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“… The table shows the number of positive ACTH responses to DDAVP according to the criteria developed by the authors in each study. Malerbi et al (1996) evaluated the response to DDAVP in terms of cortisol percent increment. …”
Section: Discussionmentioning
confidence: 99%
“…The following criteria were used to classify a positive response to desmopressin: (i) Preoperatively, plasma ACTH and serum cortisol increases of at least 30% and 20% above baseline, respectively. In the range of ACTH and cortisol concentrations usually found in patients with active Cushing's disease, this corresponds approximately to an increment of at least four times the intra‐assay coefficient of variation at baseline used in other studies (Nieman et al ., 1986; Malerbi et al ., 1993; Malerbi et al ., 1996). (ii) In the early postoperative period, the same criteria were used.…”
Section: Methodsmentioning
confidence: 99%